Art for Everyone? Mush, Multiculturalism, and the Prismatic Arts Festival - Kraus, Brittany (Theatre Research in Canada / Recherches théâtrales au Canada, 2019)
Founded in 2008 by Shahin Sayadi and Maggie Stewart, the Prismatic Arts Festival is a Halifax-based multidisciplinary arts festival that features the work of Indigenous and culturally diverse artists. This article examines the development of the Prismatic Arts Festival and the ways in which the festival has sought to negotiate, challenge, and transform Halifax’s artistic landscape by creating a model that is locally-grounded, nationally-networked, and fundamentally devoted to advancing the careers and profiles of Indigenous and culturally diverse artists in Nova Scotia and across Canada both within and outside of mainstream performance cultures. As the festival recently celebrated its tenth anniversary, this article traces the history of the Prismatic Arts Festival, its struggles and successes, and the complex negotiations the festival has made and continues to make in order to move toward a future of Canadian theatre in which cultural diversity and inclusivity are the norm, rather than the exception.